Theoretical framework and research prospect of the impact of China’s digital economic development on population - Zhou, Chunshan; Zhang, Dahao; Chen, Yu (Frontiers in Earth Science, 2022)
Against the background of social digitalization, networking, and intelligent development, the relationship between China’s digital economy and regional factors is increasingly close. This study systematically cards the relevant references of the digital economy, regional factors, and population based on the six perspectives of industry, residents’ income, urban human settlement environment, infrastructure, the real economy, and government management level to explore the influence of the digital economy on regional factors and regional factors on population. The results show that: 1) the digital economy has a bidirectional influence on the population. Digital economy can both attract population and lead to population outflow through relevant regional factors. 2) Digital economy can indirectly affect the spatial layout of population attributes by giving digital connotations to regional elements. We analyze the influence of China’s digital economic development on the population, build the influence of the digital economy on the population research framework, and put forward the research prospect of the impact of the digital economy on the population to provide a new research perspective on digital economic geography and population, as well as provide significant reference to guide the reasonable population flow and narrow the digital divide gap.